PROBLEMA PEREMPUAN DALAM MEMILIH PRODUK UNGGULAN BANK SYARIAH MANDIRI (BSM) - RAHIM, ABDUL (LPPM IAIN Parepare, 2014)
Syariah bank has developed from year to year, although it is not booming like conventional banks due to various factors. Some experienced problems in its development are the aspects of law, lack of socialization of Syariah Bank, the operational constraints, and public's understanding toward Syariah Bank is still low. All constraints should be analyzed in accordance with the facts which exist in society to have solution as an input to develop Syariah Bank for the future.